Weldability of AISI 430/AISI 1030 Steel Couples via the Synergic Controlled Pulsed (GMAW-P) and Manual Gas Metal Arc (GMAW) Welding Techniques - Teker, Tanju; Kursun, Turhan (Taylor & Francis Inc, 2011)
In this study, ferritic stainless steel (AISI 430)/medium-carbon steel (AISI 1030) couples, having two different properties of 10mm thick, were welded by using the synergic controlled pulsed (GMAW-P) and manual gas metal arc welding (GMAW) techniques. Constant wire feed speed, voltage, welding speed, and gas flow rates (3.2 m/min, 22.5 V, 4 mm/s, 16 L/min) were used in these techniques. The interface appearances of the welded samples were examined by optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and X-Ray diffraction (XRD). In order to determine mechanical properties of samples, the tensile and microhardness tests were conducted. The GMAW-P joints of AISI 430/AISI 1030 steel couples showed superior tensile strength, less grain growth, and narrower heat affected zone (HAZ) when compared with GMAW joints, and this was mainly due to lower heat input, finer fusion zone grain, and higher fusion hardness.
Keywords: GMAW-P; Mechanical; Welding